FAKTOR-FAKTOR DALAM PELAKSANAAN GERAKAN LITERASI SEKOLAH (GLS) DI SMA NEGERI 12 PEKANBARU - Delima Afrilia Manulang; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: this research was effected by several factors that are considered to greatly affect the implementation of the Literacy Movement Schools which further shortened with GLS good which is an inhibitor of factor or factor endowments in the implementation of the GLS in SMA Negeri 12 Pekanbaru. Formulation of the problem in this research is